Which Design Concept for Prestressed Steel? - Tochacek, Miloslav; Amrhein, Francis Gene (Engineering Journal, 1971)
Prestressed steel structures are those in which, during manufacture, assembly, or exploitation, deliberate stresses are produced of precise magnitude, direction, and period of duration. The most significant aims of prestressing are: enlargement of the elastic range in which the structure works; redistribution of internal stresses or forces; improvement of stability; increase of fatigue resistance; decrease in deformations; wider use of high strengthsteels. Some examples of the many types of prestressed steel structures and methods of prestressing are: rigid basic structures (girders, trusses, frames, masts, towers, etc.) prestressed by high strength tendons; systems or networks of prestressed flexible strings (hanging roofs and walls, etc.); multi-layer and hybrid beams or vessels (simultaneous use of different materials as concrete and steel, carbon steel and quenched-tempered steel, etc.); statically indeterminate structures prestressed by enforced displacement of redundant restraints (usually by enforced shifting of some redundant supports or by compelled assembly of some elements fabricated with planned dimension "inaccuracies"); removal or exploitation of residual, secondary, or other "parasite" stresses (from welding, temperature treatments, mechanical operations with steel in cold state, unwanted constructional rigidity of some details, etc.). Prestressed structures utilizing tendons are the most widely used and most economical.